How editors and publishers perceive their leadership behavior in Chilean and Spanish newsrooms. An approach from transformational leadership - Benavides, Cristóbal (2019)
In the media industry, fast innovations and increasing competition require a high degree of corporate leadership (Koryak, Mole, Lockett, et al., 2015). The study of leadership appears to be an increasingly relevant issue. This research aims to find out to what extent leaders (editors and publishers) behave and understand their roles in Chilean and Spanish newsrooms. A questionnaire was applied to measure and identify leadership traits that are considered crucial, thus making possible to acknowledge transformational leaders and differentiate efficient leaders from ineffective. The results show that editors believe they have the ability to inspire, share goals and understand what is important, in contrast with the working experiences of their employees, that often have a low opinion of media companies as places to work.